From the exhibition After Modernism to the Cómicos Gallery. The work of Portuguese gallerist Luís Serpa with architects - Gomes, L. (2022)
This article aims to show the work that the gallerist Luís Serpa carried out throughout his career with Portuguese architects, work that had its beginnings in the exhibition After Modernism. Coordinate by Serpa, the exhibition After Modernism, took place in January 1983, the most important and widely covered exhibition of the 1980s in Portugal, opened up the dialogue on post-modernism in Portugal, and, particularly in the field of architecture, allowed to become clear the different positions between the north, following a more scholastic line linked to the so-called Oporto School, and the south, without a defined line of identification, particularly through the exhibitions held in Portugal and abroad. In the sequence of the exhibition After Modernism and in this context of debating ideas Luís Serpa founded Cómicos Gallery, in which he developed an important work in the dissemination of art, design, photography and architecture. It is this path that we intend to discuss in this article.